Biomass Wastes as Precursor For The Synthesis of Carbon Nanoparticle. Issue 1 (December 2021) - Lian, Brenda Lim Ai; Lim, Steven; Yean, Pang Ling; Shuit, Siew Hoong; Kam, Huei Wong
Abstract: The development of technology and the growth in human population had resulted in a surge in energy demand and biomass waste production. Metal-air battery (MAB) is a potential energy storage technology with high theoretical energy density and safety. However, the conventional air cathode material synthesized from carbon nanotube (CNT) is rather costly. In this study, several biomass wastes such as oil palm empty fruit bunch (OPEFB), garlic peel (GP) and oil palm frond (OPF) were investigated to identify a suitable greener and efficient precursor to syntheelesize carbon nanoparticle as air electrode material for MAB. The carbon materials were synthesized through carbonization of precursor at different temperatures of 450 °C, 600 °C, and 700 °C before activation with potassium hydroxide (KOH) through wet impregnation method. The materials synthesized were evaluated based on its chemical and physical properties through characterization using thermogravimetric analysis (TGA), fourier transform infrared spectroscopy (FTIR), scanning electron microscopy with energy dispersion x-ray (SEM-EDX), field emission scanning electron microscopy (FESEM) and Brunauer-Emmet-Teller (BET) analysis. Based on the experiments conducted, it was found that the suitable precursor was the OPF as it displayed a better tunability for enhanced electrical conductivity as it was able to achieve smaller sized particles with higher specific surface area of 548.26 m 2 /g and hierarchical porous structure at 700 °C compared to OPEFB and GP. This study proved that OPF could be a promising alternative to CNT as an electrode material which is more sustainable and cost efficient for energy storage application such as MAB.